Tourist's perceptions of crowding at recreational sites: the case of the Perhentian Islands. Issue 1 (2nd January 2017) - Rasoolimanesh, S. Mostafa; Jaafar, Mastura; Marzuki, Azizan; Abdullah, Shardy
Abstract: This study examines the effects of tourist socio-demographic characteristics and socio-behavioural factors on tourists' perceived crowding. A questionnaire in both Bahasa Malay and English languages was administered to collect data from tourists visiting the Perhentian Islands, Malaysia. The findings revealed a significant effect for education and age on perceived crowding. In addition, the results highlighted the significant effect of interactions with the local community and satisfaction with accommodation on tourists' perceived crowding. However, the results could not support a significant effect for gender or the perceived social impacts of tourism on the perception of crowding. Given the paucity of studies investigating the factors contributing to perceived crowding, the findings of this study make a significant contribution to the literature. Moreover, this study has a number of practical implications for the local authorities.